The Four Levels of Implementing Mathematical Rap in Your Classroom - Perez, Rodney Andres (Ohio Journal of School Mathematics, 2020)
Accessing cultural funds of knowledge using hip-hop can increase engagement and can be implemented in the classroom at various levels. This paper provides a framework for implementing mathematical rap in mathematics classrooms. Real classroom examples are provided to illustrate use-cases and student products.